Thermoprotection of Bacillus subtilis by Exogenously Provided Glycine Betaine and Structurally Related Compatible Solutes: Involvement of Opu Transporters - Holtmann, Gudrun (American Society for Microbiology, 2004)
Bacillus subtilis possesses five osmotically regulated transporters (Opu) for the uptake of various compatible solutes for osmoprotective purposes. We have now found that compatible solutes also function as thermoprotectants for B. subtilis. Low concentrations of glycine betaine enhanced the growth of the B. subtilis wild-type strain JH642 at its maximal growth temperature (52°C) but did not allow an extension of the upper growth limit. A similar enhancement in the growth of B. subtilis was also observed by the addition of several other compatible solutes that are structurally related to glycine betaine or by the addition of proline. Each of these compatible solutes was taken up under heat stress by the cell through the same Opu transporters that are used for their acquisition under osmostress conditions. Northern blot analysis revealed a moderate increase in transcription of the structural genes for each of the Opu transport systems in cells that were propagated at 52°C. In contrast, the uptake level of radiolabeled glycine betaine was very low under high-temperature growth conditions but nevertheless allowed the buildup of an intracellular glycine betaine pool comparable to that found in cells grown at 37°C in the absence of salt stress. Although exogenously added glutamate has only a limited osmoprotective potential for B. subtilis, it was found to be a very effective thermoprotectant. Collectively, our data demonstrate thermoprotection by a variety of compatible solutes in B. subtilis, thus ascribing a new physiological function for this class of compounds in this microorganism and broadening the physiological role of the known osmoprotectant uptake systems (Opu).